Temperature and magnetic field-assisted switching of magnetization and observation of exchange bias in YbCrO3 nanocrystals - Gupta, Preeti; Poddar, Pankaj (Inorganic Chemistry, 2015)
In this paper, we demonstrate an interesting feature in YbCrO3 (YCO) nanocrystals, in which the material shows temperature and external magnetic field-assisted switching (a complete sign reversal) of zero field cooled magnetization (M-ZFC) and observation of exchange bias (EB) as a result of competing spin interaction at low temperature. This feature can be applied in nonvolatile memories, where, simply by changing the magnitude of the H-ext and T, the polarity of the magnetization can be switched between negative and positive. We also observed negative magnetization in YCO. Our results showed that, below its Neel temperature (T-N approximate to 119 K), the M-ZFC crosses over to negative sign for H < 1000 Oe. At 60 K, YCO showed a significant negative M-ZFC approximate to -0.05 emu/g (at 100 Oe) due to the competing effects of Yb3+, Cr3+ spins, thermal activation energy, and Hext. At further lower temperatures, the M-ZFC showed a crossover to positive values, and the crossover temperature showed the dependence on H-ext (similar to 19 K for 100 Oe curve). The YCO also showed H-ext T-dependent H-EB, which changed its sign with T. The observed T-dependent sign reversal in the EB was closely associated with the sign reversal of M-ZFC. The symmetric shift in field-cooled isothermal hysteresis curves confirmed that the observed EB was not due to the unsaturated minor loop. The training cycle further confirmed that the H-EB value decreased to similar to 2% of the initial value of observed EB, which was very small compared to the observed H-EB in YCO, which indicated stable spin configuration at the locally formed ferromagnetic/antiferromagnetic interface.